2014
DOI: 10.1208/s12249-014-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of Absorption Modeling to Predict Bioequivalence Outcome of Two Batches of Etoricoxib Tablets

Abstract: Abstract. As part of the overall product development and manufacturing strategy, pharmaceutical companies routinely change formulation and manufacturing site. Depending on the type and level of change and the BCS class of the molecule, dissolution data and/or bioequivalence (BE) may be needed to support the change for immediate release dosage forms. In this report, we demonstrate that for certain weakly basic low-solubility molecules which rapidly dissolve in the stomach, absorption modeling could be used to j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 15 publications
0
47
0
1
Order By: Relevance
“…Physiologically based pharmacokinetic (PBPK) modeling has been utilized to assess the food effect 33,34 , drug-drug interaction [35][36][37] , inter-batch quality variation 38 , in vivo performance in subpopulation 18 , and bioequivalence for generic drug evaluation 18,38,39 . In the current study, we extended such a PBPK approach to assess the in vivo PK and bioequivalence associated with formulation release mechanism change for oral ER venlafaxine HCl dosage forms based on an openable matrix design.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically based pharmacokinetic (PBPK) modeling has been utilized to assess the food effect 33,34 , drug-drug interaction [35][36][37] , inter-batch quality variation 38 , in vivo performance in subpopulation 18 , and bioequivalence for generic drug evaluation 18,38,39 . In the current study, we extended such a PBPK approach to assess the in vivo PK and bioequivalence associated with formulation release mechanism change for oral ER venlafaxine HCl dosage forms based on an openable matrix design.…”
Section: Discussionmentioning
confidence: 99%
“…Mitra and colleagues generated dissolution profiles in multimedia to support a site transfer for etoricoxib, which is a BCS II drug [28]. The F2 similarity test failed at pH 4.5 and 6.8.…”
Section: Integrating In Vitro and In Silico Modelling-orbito Experienmentioning
confidence: 99%
“…For example, Zhang et al demonstrated how oral absorption/PBPK modeling could be used to understand the in vivo performance of generic IR and XR carbamezepine formulations and identify the important characteristics in the release mechanisms that should be reflected in a dissolution test (33). More recently, Mitra et al described the use of models to assess the impact of dissolution differences observed between batches manufactured at different sites for etoricoxib (34). The simulations showed that the dissolution differences (outside f 2 bounds) observed at pH 4.5 and 6.8 during multimedia testing were not clinically relevant, while the dissolution at pH 1.2 (f 2 > 50) would be a better predictor of clinical performance.…”
Section: Selection Of Appropriate Tools For Establishing Crsmentioning
confidence: 99%